1985
DOI: 10.1136/gut.26.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Liver in obesity.

Abstract: SUMMARY We report on clinical, nutritional, and hepatic histological findings in 50 non-selected obese subjects (mean overweight +74%; range +21-138%). The pathogenesis of the liver damage was assessed with the help of multidimensional analysis of a number of clinical variables. According to the severity of the hepatic lesions, the patients have been ranged in five groups: 0 (normal liver) 10%; I (fatty liver) 48%; II (fatty hepatitis) 26%; III (fatty fibrosis) 8%; IV (fatty cirrhosis) 8%. The more severe chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
4

Year Published

1995
1995
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(55 citation statements)
references
References 16 publications
1
50
0
4
Order By: Relevance
“…In fact, we have not considered as steatosis the pattern of slight increase of the liver echogenicity and echo discrepancy between liver and kidney that other authors have classi®ed as mild steatosis, 3 because this ®gure may be equivocal in obesity. The present data show a direct although weak correlation between the degree of obesity and that of steatosis, according with several observations, 8,21,23,24,36,37 but opposite results are reported, 6,38 possibly related to the minor severity of weight excess of the subjects. On the other hand, as far as the Table 3 The biochemical parameters in the subjects, grouped according to the pubertal stage and to the presence (S) or not (N) of steatosis (* P`0.001 vs stages II ± III; **P`0.001 vs stages IV ± V; {P`0.05, {P`0.01, §P`0.001, N vs S) Liver steatosis in juvenile obesity G Guzzaloni et al duration of obesity is concerned, which we have not considered for the lack of reliable data, there are many concerns in the literature: in fact it has been suggested that both a long, 19,20,23,24,36,38 and a shorter duration 22 could be independent cofactors for determining steatosis, and also that no correlation exists with the duration as such, at least in adults.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In fact, we have not considered as steatosis the pattern of slight increase of the liver echogenicity and echo discrepancy between liver and kidney that other authors have classi®ed as mild steatosis, 3 because this ®gure may be equivocal in obesity. The present data show a direct although weak correlation between the degree of obesity and that of steatosis, according with several observations, 8,21,23,24,36,37 but opposite results are reported, 6,38 possibly related to the minor severity of weight excess of the subjects. On the other hand, as far as the Table 3 The biochemical parameters in the subjects, grouped according to the pubertal stage and to the presence (S) or not (N) of steatosis (* P`0.001 vs stages II ± III; **P`0.001 vs stages IV ± V; {P`0.05, {P`0.01, §P`0.001, N vs S) Liver steatosis in juvenile obesity G Guzzaloni et al duration of obesity is concerned, which we have not considered for the lack of reliable data, there are many concerns in the literature: in fact it has been suggested that both a long, 19,20,23,24,36,38 and a shorter duration 22 could be independent cofactors for determining steatosis, and also that no correlation exists with the duration as such, at least in adults.…”
Section: Discussionsupporting
confidence: 63%
“…3,4 In adults the severity of steatosis has been correlated with the degree of obesity, 5 ± 8 although opposite results have been reported, 9 ± 11 and with the serum levels of free fatty acids, as well as glycemia and insulinemia. 6,12,13 However, no correlation with liver biochemical abnormalities was found. 10,12,14 ± 16 In childhood and adolescent obesity the fatty change of the liver has also been well documented, although with different values of prevalence, and correlated with duration and degree of obesity and with serum levels of transaminases.…”
Section: Introductionmentioning
confidence: 71%
“…This suggests that the rapid mobilization of intra-and extrahepatic fat stores, probably associated in some cases with de®cient protein diet during weight loss, may contribute to the aggravation of preexistent liver steatosis in these subjects. 20,24 Liver insults by hepatotoxic drugs, moderate alcohol intake or viral infections are retrospectively dif®cult to exclude and may explain part of the in¯ammatory changes observed in the second liver biopsy. Nevertheless, when hepatitis was present, a further investigation was performed on the liver fragment in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…As recently reviewed 55 , these findings were confirmed in further studies. 44,56,57 In an autopsy study, steatohepatitis was found in 18.5% of markedly obese patients in contrast to only 2.7% of lean patients, while severe fibrosis was found in 13.8% versus 6.6% respectively. 58 Large series of liver biposies performed in severely obese subjects submitted to bariatric surgery have been recently published.…”
Section: The Association Of Nash With Obesitymentioning
confidence: 98%
“…The observation that some obese individuals presented a liver disease histologically indistinguishable from alcoholic liver disease itself had long been recognized. [42][43][44][45][46][47][48][49] Interestingly, it has been recently demonstrated that obesity also increases the risk of liver disease induced by either alcohol 50 or chronic hepatitis C. [51][52][53] In a literature survey of 41 original articles comprising information on liver morphology in 1515 morbidly obese patients, liver biopsy was considered as normal in only 12% of the cases. 54 The most frequent abnormality reported was fatty changes present in 80% of the biopsies; portal inflammation was also common (33%) while portal or periportal fibrosis was observed in 29%.…”
Section: The Association Of Nash With Obesitymentioning
confidence: 99%